2019
DOI: 10.4049/jimmunol.1800598
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 Signaling Selectively Regulates IFN-α: Role of β-Arrestin 2 in IFNAR1 Internalization

Abstract: An integral component of the antiviral response, Type I IFNs require regulation to modulate immune activation. We identify β-arrestin 2 as a key modulator of Type I IFN in primary human macrophages, an essential component of the innate immune response. β-arrestin 2 was selectively activated by CCL2/CCR2 signaling, which induced a decrease in IFN-α, but not IFN-β expression. siRNA knockdown of β-arrestin 2 demonstrated its role in IFNAR1 internalization, as well as STAT1 and IRF3 activation. As a result, cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Recent data has shown that CB 1 R and CB 2 R receptors have opposite effects. Indeed CB 1 R antagonists and CB2R agonists both protect the heart against clozapine-toxicity (190). Thus, CB 1 R antagonist reduces DOX-induced cardiotoxicity and decreased cortical cerebral infarction (191).…”
Section: Cannabidiolmentioning
confidence: 99%
“…Recent data has shown that CB 1 R and CB 2 R receptors have opposite effects. Indeed CB 1 R antagonists and CB2R agonists both protect the heart against clozapine-toxicity (190). Thus, CB 1 R antagonist reduces DOX-induced cardiotoxicity and decreased cortical cerebral infarction (191).…”
Section: Cannabidiolmentioning
confidence: 99%
“…CCL2, also named monocyte chemoattractant protein 1, is a chemotactic cytokine for monocytes (14) and T cells (15), which are the main target cells of HIV-1. CCL2 decreases interferon-alpha expression (16), and promotes HIV/SIV replication by up-regulation of surface C-X-C motif chemokine receptor 4 expression (17).…”
Section: Introductionmentioning
confidence: 99%
“…phosphorylated GPCRs and the two main components of the clathrin-dependent endocytic machinery, AP-2, and clathrin (96)(97)(98). In support of this, it was recently reported that silencing RNA against b-arrestin 2, but not barrestin 1, restored IFN-a levels of SIV infected macrophages in a CCL2/CCR2-dependent manner (99). They further showed that b-arrestin2 was required for IFNAR1 internalization, in agreement with the first implication of AP2 in IFNAR1 endocytosis (83).…”
Section: Beginning Of the Journey: En Route To The Endosomementioning
confidence: 81%